Transformation of Early Childhood Education: A Descriptive Quantitative Analysis of Critical Thinking Skill Development in Banten Province, Indonesia - Rohita, Rohita; Roebianto, Adiyo; Yetti, Elindra (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the perceptions of PAUD teachers in Lebak, Banten, about critical thinking skills in learning for children aged 4-6 years, learning strategies, and challenges faced. A descriptive quantitative approach was used with an open-ended questionnaire filled out by 131 teachers. Data were analyzed using descriptive statistics with presentation in the form of visual graphs. The results showed that teachers' understanding of critical thinking indicators varied, with 39.6% understanding critical thinking more as the ability to analyze, 14.4% as interpretation, 12.6% as evaluation, 8.2% as inference, 5.4% as explanation, and 4.5% as self-regulation. Teachers emphasized analysis and interpretation through interactive methods, while evaluation and inference were less applied. The novelty of this study lies in the mapping of teachers' understanding based on critical thinking indicators and their impact on learning strategies. Recommendations for training based on direct practice and reflection to improve the implementation of critical thinking evenly are contributions to the research results as well as being the basis for improving policies and developing teacher training in areas with low HDI.